Reduced Mid1 Expression and Delayed Neuromotor Development in daDREAM Transgenic Mice - Dierssen, Mara; Fedrizzi, Laura; Gomez-Villafuertes, Rosa; Martinez de Lagran, Maria; Gutierrez-Adan, Alfonso; Sahun, Ignaci; Pintado, Belen; Oliveros, Juan C.; Dopazo, Xose M.; Gonzalez, Paz; Brini, Marisa; Mellstrom, Britt; et al. (Frontiers in Molecular Neuroscience, 2012)
DREAM (downstream regulatory element antagonist modulator) is a Ca2+-binding protein that binds DNA and represses transcription in a Ca2+-dependent manner. Previous work has shown a role for DREAM in cerebellar function regulating the expression of the sodium/calcium exchanger 3 (NCX3) in cerebellar granular neurons to control Ca2+ homeostasis and survival of these neurons. To achieve a global view of the genes regulated by DREAM in the cerebellum, we performed a genome-wide analysis in transgenic cerebellum expressing a Ca2+-insensitive/CREB-independent dominant active mutant DREAM (daDREAM). Here we show that DREAM regulates the expression of the midline 1 (Mid1) gene early after birth. As a consequence, daDREAM mice exhibit a significant shortening of the rostro-caudal axis of the cerebellum and a severe delay in neuromotor development early after birth. Our results indicate a role for DREAM in cerebellar function.